Effectiveness of Subsidy Policies on Livestock Feed and Production - Chen, Lucy (International Journal of Livestock Policy, 2024)
Purpose: The general purpose of this study was to evaluate the effectiveness of subsidy policies on livestock feed and production. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to the effectiveness of subsidy policies on livestock feed and production. Preliminary empirical review revealed that well-targeted subsidy policies significantly enhanced the efficiency and sustainability of livestock production by stabilizing feed costs, which helped farmers maintain consistent production levels and invest in advanced technologies. These investments led to improved productivity and animal welfare, contributing to long-term agricultural sustainability. The study also highlighted the environmental benefits of subsidies promoting sustainable practices and emphasized the importance of equitable distribution to ensure smallholder and marginalized farmers benefited from these policies. This inclusive approach ensured broader economic and social development within the agricultural sector. Unique Contribution to Theory, Practice and Policy: The Theory of Planned Behaviour, Resource- Based View and Institutional Theory may be used to anchor future studies on subsidy policies on livestock feed and production. The study concluded with several key recommendations. It emphasized the need for a nuanced understanding of subsidy impacts, suggesting future research should develop models incorporating economic, environmental, and social variables. Practically, it recommended enhancing subsidy programs to be more targeted and equitable, ensuring smallholder and marginalized farmers benefit fairly. The study also highlighted aligning subsidies with sustainability goals and increasing funding for agricultural innovation. International cooperation and policy harmonization were suggested to prevent market distortions and promote fair trade. Additionally, it stressed incorporating stakeholder feedback and continuous monitoring and evaluation to ensure policies remain effective and relevant.